Smart Apps Creator 3 to improve student learning outcomes during the pandemic of COVID-19 - Rori Khoirudin; A. Ashadi; Mohammad Masykuri (University of Muhammadiyah Malang, 2021)
Due to the COVID-19 pandemic, learning activities have encountered obstacles. One of the impacts was the low learning outcomes achieved by students. The purpose of this study was to improve the learning outcomes of junior high school students during the physical distancing period by implementing problem-based learning through Smart Apps Creator 3. This Classroom Action Research (CAR) used Smart Apps Creator 3 as the platform during learning activities of junior high school students. The research subjects were junior high school students (VIII graders of SMP Negeri 8 Surakarta) with a total number of students was 32 which consisted of 16 males and 16 females. The results showed that the application of Smart Apps Creator 3 has improved students’ learning outcomes. It has been proven that the average test score increased from 73.43 (pre-cycle) to 85.56 (cycle II). Moreover, the N gain score obtained was 0.45 (categorized as sufficient). In addition, the percentages of classical learning completeness were 59.37% (pre-cycle) and 93.75% (cycle II). Thus, the Smart Apps Creator 3 can improve student learning outcomes.